Gambaran Gambaran Pelayanan Swamedikasi Oleh Apoteker Di Kota Palu - Manikam, Nurintan Kurnia; Rumi, Amelia; Parumpu, Firdawati Amir (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2021)
A good self-medication service is self-medication carried out by drug experts, namely pharmacists to optimize drug use and improve health. At the same time, pharmacists are also expected to be able to provide consultations to patients and monitor any problems that may occur during drug use, which are called drug-related problems (Medication error). The purpose of this study was to determine the description of self-medication services by pharmacists in the city of Palu based on the categories of extracting information, drug selection and drug information. The research method used is descriptive qualitative cross sectional and the sampling method is purposive sampling. The respondent's criteria are pharmacists who had activated SIPA and practised in pharmacies along are willing to signs an informed consent form. Based on these criteria, had obtained 86 samples of pharmacists in pharmacies in Palu City. The instrument used is using a questionnaire in the form of Google Form which had been tested for validity and reliability testing and the data obtained is evaluated descriptively. The results showed that pharmacists in pharmacies in Palu City had carried out self-medication services for extracting information by 83.60%, drug selection by 95.35% and providing drug information by 89.66%. The conclusion of this studied is that pharmacists in pharmacies had carried out self-medication serviced properly according to variables.